Investigation of animal anthrax outbreaks in the human–animal interface at risky districts of Bangladesh during 2016–2017 - Islam, SK Shaheenur; Chakma, Shovon; Akhter, A. H. M. Taslima; Ibrahim, Nelima; Talukder, Faisol; Chowdhuary, Golam Azam (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The objective of the study was to explore the outbreak situation in terms of animal, place, and time towards minimizing the risk of animal infection at the source in future and subsequent spillover in human in the endemic rural settings. Methodology: An outbreak investigation team from the Department of Livestock Services visited in each of the outbreak sites to explore the event towards strengthening the control program in the future. Meat samples of the infected slaughtered animals were collected to confirm the causal agent of the animal outbreak using polychrome methylene blue microscopic examination technique. Participatory epidemiology tool such as semi-structured interview had been used in these investigations to realize the knowledge and practices of local people/cattle keepers on anthrax control and prevention in animal and human as well. Results: All identified affected human cases had been confirmed as a history of contact with the animal carcasses or handling/processing with infected meat. The level of awareness at the community level was not satisfactory for the prevention and control of anthrax at the source and further spillover in human. The infected slaughtered animals found to be in non-vaccinated status during the outbreak investigation and uncontrolled animal movement is considered to be responsible for new outbreaks in a vaccinated zone where enforcement of veterinary legislation is inadequate. Conclusion: A comprehensive preparedness and response strategy is to be obligatory for prevention, control and respond on anthrax in Bangladesh. Maximum vaccination coverage in the animal, increase community awareness of animal and human anthrax are also demanded for transmission of anthrax from animal to human. http://doi.org/10.5455/javar.2018.e290